Application of organic amendment and Trichoderma sp. to control basal Sclerotium rolfsii on peanut grown on partially degraded land - Suheri, H; Isnaini, M; Rohyadi, A (Brawijaya University, 2014)
An experiment involving the application of organic matters, either fresh or composted, application of bioagent Trichoderma sp. was conducted to suppress basal stem rot caused by S. rolfsii on peanut. The research was conducted at dry land in Amor-Amor North Lombok District with the pump water well system. The experiments were arranged as split plot design with the main plot was pathogen inoculation and non pathogen inoculation. As sub-plot were the addition of organic matters and or addition of bioagent Trichoderma sp. plus two control treatments. Pathogen S. rolfsii applied as fragment mycelia of 1 x 10 6 fragment/ mL with the number of 10 L/plot. Inoculation of the pathogen was conducted when seedlings were about one month old. The bioagent Trichoderma sp. was applied 50 g/plot as powder in the same time of organic matters application (before planting the seeds). The results showed that application of composted organic matters reduced disease incidence 6-10%, while application as fresh organic matters reduced 1-6%. Combination between application of bioagent Trichoderma sp. with fresh and or composted organic matters suppressed disease incidence 8-10% and 8-12% respectively. Application of bioagent alone on planting medium reduced disease incidence 7.5%. Application of composted organic matters with bioagent Trichoderma sp. increased the number of fresh plant biomass 4.93-11.78 kg.